The effects of different warm-up volumes on the 100-m swimming performance: A randomized crossover study - Neiva, H. P.; Marques, M. C.; Barbosa, T. M.; Izquierdo, M.; Viana, J. L.; Teixeira, A. M.; Marinho, D. A. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to compare the effect of 3 different warm-up (WU) volumes on 100-m swimming performance. Eleven male swimmers at the national level completed 3 time trials of 100-m freestyle on separate days and after a standard WU, a short WU (SWU), or a long WU (LWU) in a randomized sequence. All of them replicated some usual sets and drills, and the WU totaled 1,200 m, the SWU totaled 600 m, and the LWU totaled 1,800 m. The swimmers were faster after the WU (59.29 seconds; confidence interval [CI] 95%, 57.98-60.61) and after the SWU (59.38 seconds; CI 95%, 57.92-60.84) compared with the LWU (60.18 seconds; CI 95%, 58.53-61.83). The second 50-m lap after the WU was performed with a higher stroke length (effect size [ES] = 0.77), stroke index (ES = 1.26), and propelling efficiency (ES = 0.78) than that after the SWU. Both WU and SWU resulted in higher pretrial values of blood lactate concentrations [La-] compared with LWU (ES = 1.58 and 0.74, respectively), and the testosterone:cortisol levels were increased in WU compared with LWU (ES = 0.86). In addition, the trial after WU caused higher [La-] (ES = 0.68) and testosterone:cortisol values compared with the LWU (ES = 0.93). These results suggest that an LWU could impair 100-m freestyle performance. The swimmers showed higher efficiency during the race after a 1200-m WU, suggesting a favorable situation. It highlighted the importance of the [La-] and hormonal responses to each particular WU, possibly influencing performance and biomechanical responses during a 100-m race.